Fiscal Rules in Ensuring the Debt Security of Ukraine - Koliada Tetiana A.; Bench Liliia Ya.; Pozhytkova Polina A. (Bìznes Inform, 2023)
The aim of the article is to deepen and develop the scientific foundations of disclosure of the essence and significance of fiscal rules in the budget process, the features of their practical application in the countries of the world in the context of strengthening the debt security of Ukraine. The article systematizes fiscal rules by kinds, provides an essential characterization, identifies the disadvantages and advantages of their practical application in order to manage the debt security of the State. The popularity and frequency of application of various kinds of fiscal rules in the budget process of 106 countries of the world for the period from 1990 to 2021 are determined, some visual graphs are built. The distribution of fiscal rules by kinds in the context of economic groups of the countries of the world is carried out, an assessment of their effectiveness in the implementation of counter-cyclical fiscal policy is provided. The practice of using fiscal rules in the budget process of Ukraine is disclosed, the reasons for violation of their marginal indicators during military aggression are determined. The need to use a combination of different kinds of fiscal rules in order to achieve positive effects on debt security and level the cyclical nature of fiscal policy is emphasized. Proposals for improving the process of public debt management in the context of ensuring the optimal level of debt security of Ukraine are substantiated. Prospect for further research in this direction is to prove the need to restore the system of fiscal rules after the end of the war and bring it to the requirements of the European Union, taking into account the European integration vector of Ukraine’s development.